Evaluation of the Supplementary Feeding Program (PMT) to reduce stunting rates in toddlers - Gusman, Gusman; Tasya, Amalia; Nurcahyanti, Khusnul Khotimah Arum; Tirtawati, Gusti Ayu (Pt. Anagata Sembagi Education, 2025)
Stunting is a serious health problem that is still high in Indonesia, with a prevalence reaching 27.6% in 2021. This condition is caused by chronic malnutrition and repeated infections that affect children's physical, cognitive, and motor growth. The Supplementary Feeding Program (PMT) has been implemented as one of the interventions to improve the nutritional status of toddlers and reduce stunting rates. Studies show that PMT based on fortification and local food can significantly increase children's weight and height. However, the effectiveness of this program still faces various challenges, including limited resources, coordination between stakeholders, and social and cultural factors that influence the acceptance of the program in the community. This study uses a qualitative approach with a case study method to evaluate the effectiveness of PMT in reducing stunting rates. The results show that the success of the program is highly dependent on nutrition education, the quality of additional food, and the involvement of health workers and the community. To increase the effectiveness of PMT, budget optimization, health worker training, and adaptive strategies based on local needs are needed. With a more comprehensive approach, this program is expected to run more optimally, reduce stunting rates, and improve the quality of life of children in Indonesia in a sustainable manner